2004
DOI: 10.1093/jnci/djh067
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Breast Cancer Detection and Mammography Recall Rates After the Introduction of a Computer-Aided Detection System

Abstract: The introduction of computer-aided detection into this practice was not associated with statistically significant changes in recall and breast cancer detection rates, both for the entire group of radiologists and for the subset of radiologists who interpreted high volumes of mammograms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
160
1
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(177 citation statements)
references
References 17 publications
7
160
1
9
Order By: Relevance
“…In the laboratory, a target will be usually present on 50% of trials -100% for identification tasks. In stark contrast, targets are very rare in a variety of socially important searches such as airport security (Rubenstein, 2001) or medical screening tasks (Gur et al, 2004;Pisano et al, 2005;Smith & Turnbull, 1997). We previously demonstrated that miss error rates were far higher at 1% target prevalence than at 50% prevalence (Wolfe, Horowitz, & Kenner, 2005).…”
mentioning
confidence: 99%
“…In the laboratory, a target will be usually present on 50% of trials -100% for identification tasks. In stark contrast, targets are very rare in a variety of socially important searches such as airport security (Rubenstein, 2001) or medical screening tasks (Gur et al, 2004;Pisano et al, 2005;Smith & Turnbull, 1997). We previously demonstrated that miss error rates were far higher at 1% target prevalence than at 50% prevalence (Wolfe, Horowitz, & Kenner, 2005).…”
mentioning
confidence: 99%
“…Breast cancer is the most prevalent cancer in women and is the second leading cause of cancer deaths in women (7). In North America, screening mammography has a false negative rate of 20 to 30% (8,9) and a recall rate of about 10% (10). With a disease prevalence of about 0.3% (11), the vast majority of those recalled will not have cancer.…”
mentioning
confidence: 99%
“…Breast cancer has low prevalence (0.3%), 16 and in low prevalence conditions, miss error rates are known to be high 17 . Ultrasound is not the primary diagnostic tool for DCIS which are commonly detected as micro‐calcifications on a mammogram.…”
Section: Discussionmentioning
confidence: 99%